Epidemiology of injuries in National Collegiate Athletic Association women's lacrosse: 2014-2015 through 2018-2019 - Bretzin, A. C.; D'Alonzo, B. A.; Chandran, A.; Boltz, A. J.; Robison, H. J.; Collins, C. L.; Morris, S. N. (Journal of Athletic Training, 2021)
Context: Lacrosse is an increasingly popular sport; the number of teams participating in collegiate women's lacrosse has increased by 21.4% in the past 5 years. Background: The growth of National Collegiate Athletic Association women's lacrosse, coupled with the ongoing discussions surrounding protective equipment, necessitates further epidemiologic studies in this population. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios with 95% CIs were used to examine differential injury rates. Results: The overall injury rate was 4.99 per 1000 athlete exposures. Less than 30% of injuries were time-loss injuries; injuries were most commonly attributed to noncontact (26.6%) and overuse (25.2%) mechanisms. The most commonly reported specific injuries were lateral ligament complex tears (ankle sprains; 9.1%), concussions (7.2%), and hamstring tears (3.8%). Summary: Findings from this study were consistent with the existing epidemiologic evidence in previous studies. Injury incidence in practices, in preseason, and as a result of player contact warrant further attention in this population.